<h3>
Answer: Geometric</h3>
===============================================
Explanation:
To go from term to term, we are multiplying by 2
-7 * 2 = -14
-14 * 2 = -28
-28 * 2 = -56
This means the common ratio is 2 and this sequence is geometric.
---------
Alternatively, you can divide each term by its prior term
-56/(-28) = 2
-28/(-14) = 2
-14/(-7) = 2
Each time we get the same result showing the common ratio is 2.
Answer:
-2x+3y =1.......(1)
y=3x-9........(2)
Now,
putting the value of y in equation (1),
-2x+3(3x-9)=1
or,-2x+9x-27=1
or,7x-27=1
or,7x=28
x= 4
Now putting the value of X in equation (2),
y=3×4-9
= 12-9
=3
(x,y)=(4,3)
Answer:
2 1/6 miles
Step-by-step explanation:
1 1/2 miles + 2/3 miles = 2 1/6 miles
I... don’t know? How many hours is he working a year? How many days is he working?
For this case, what we are going to do is use the following property:
Multiply an equation by a scalar.
In this case, the scalar will be:
k = -2
We have then that equation 2 will be:
k * (4x + y) = k * 1
-2 * (4x + y) = - 2 * 1
-8x-2y = -2
Answer:
The property that justifies this manipulation is:
Multiply an equation by a scalar.